Hepatic gene expression in flounder chronically exposed to multiply polluted estuarine sediment: Absence of classical exposure ‘biomarker’ signals and induction of inflammatory, innate immune and apoptotic pathways - Leaver, Michael; Diab, Amer; Boukouvala, Evridiki; Williams, Tim D; Chipman, James Kevin; Moffat, Colin F; Robinson, Craig D; George, Stephen (Aquatic Toxicology, 2010)
The effects of chronic long term exposure to multiply-polluted environments on fish are not well understood, but environmental surveys suggest that such exposure may cause a variety of pathologies, including cancers. Transcriptomic profiling has recently been used to assess gene expression in European flounder (Platichthys flesus) living in several polluted and clean estuaries. However, the gene expression changes detected were not unequivocally elicited by pollution, most likely due to the confounding effects of natural estuarine ecosystem variables. In this study flounder from an uncontaminated estuary were held on clean or polluted sediments in mesocosms, allowing control of variables such as salinity, temperature, and diet. After 7 months flounder were removed from each mesocosm and hepatocytes prepared from fish exposed to clean or polluted sediments. The hepatocytes were treated with benzo(a)pyrene (BAP), estradiol (E2), copper, a mixture of these three, or with the vehicle DMSO. A flounder cDNA microarray was then used to measure hepatocyte transcript abundance after each treatment. The results show that long term chronic exposure to a multiply-polluted sediment causes increases in the expression of mRNAs coding for proteins of the endogenous apoptotic program, of innate immunity and inflammation. Contrary to expectation, the expression of mRNAs which are commonly used as biomarkers of environmental exposure to particular contaminants were not changed, or were changed contrary to expectation. However, acute treatment of hepatocytes from flounder from both clean and polluted sediments with BAP or E2 caused the expected changes in the expression of these biomarkers. Thus transcriptomic analysis of flounder exposed long-term to chronic pollution causes a different pattern of gene expression than in fish acutely treated with single chemicals, and reveals novel potential biomarkers of environmental contaminant exposure. These novel biomarkers include Diablo, a gene involved in apoptotic pathways and highly ...